Pengaruh Pengetahuan Santri Mengenai Akad Wadiah terhadap Minat Menabung di Bank Syariah: (Studi Kasus Pondok Pesantren An Nur Bantul Yogyakarta) - Nurhasanah, Fatim; Kurniawan, M. Arif; Jalil, Abdul (Quranomic: Jurnal Ekonomi dan Bisnis Islam, 2022)
This research aimed to determine the effect of students' knowledge of wadiah contracts on interest in saving in Islamic banks. This research was a quantitative study with a population of santri in Islamic boarding school An Nur Bantul, Yogyakarta. This research used a sample of 50 santri respondents. Data collection techniques used online and manual questionnaires. The data analysis requirements test used was the validity test and the reliability test. The classical assumption test was the normality test, the heteroscedasticity test. And the hypothesis test was the t test and R² test. Data processing using simple linear regression analysis. The research results indicated that there was an influence of knowledge on interest in saving. Where was the knowledge of students (X) with a significant value level of 0.000 < 0.05 which was declared to have fulfilled the requirements to be a supporting variable for interest in saving (Y). The R² value of 0.665 or 66.5% which showed the value of saving interest was influenced by the knowledge of students about wadiah contracts. While the remaining 33.5% the knowledge value of students was influenced by other factors because these factors also affected the interest in saving.